Unraveling the treasure trove of phytochemicals in mitigating the Salmonella enterica infection - Soni, Saurabh; Gambhir, Lokesh; Sharma, Gaurav; Sharma, Asha; Kapoor, Neha (Folia microbiologica, 2025)
Foodborne diseases triggered by various infectious micro-organisms are contributing significantly to the global disease burden as well as to increasing mortality rates. Salmonella enterica belongs to the most prevalent form of bacteria accountable for significant burden of foodborne illness across the globe. The conventional therapeutic approach to cater to Salmonella enterica-based infections relies on antibiotic therapy, but the rapid emergence of the antibiotic resistance strains of Salmonella sp. necessitates the development of alternative treatment and prevention strategies. In light of this growing concern, the scientific community is rigorously exploring novel phytochemicals harnessed from medicinally important plants as a promising approach to curb Salmonella enterica infections. A variety of phytochemicals belonging to alkaloids, phenols, flavonoid, and terpene classes are reported to exhibit their inhibitory activity against bacterial cell communication, membrane proteins, efflux pumps, and biofilm formation among drug resistant Salmonella strains. The present review article delves to discuss the emergence of antibiotic resistance among Salmonella enterica strains, various plant sources, identification of phytochemicals, and the current state of research on the use of phytochemicals as antimicrobial agents against Salmonella enterica, shedding light on the promising potential of phytochemicals in the fight against this pathogen.
Keywords: antibakteriální látky; Animals; Salmonella enterica; lidé; fytonutrienty; Phytochemicals; Drug Resistance, Bacterial; nemoci přenášené potravou; Humans; Foodborne Diseases; zvířata; salmonelóza; Anti-Bacterial Agents; bakteriální léková rezistence; Salmonella Infections